DIVERSIDAD DE MAMÍFEROS EN CAFETALES Y SELVA MEDIANA DE LAS CAÑADAS DE LA SELVA LACANDONA, CHIAPAS, MÉXICO - Cruz-Lara, Laura E.; Lorenzo, Consuelo; Soto, Lorena; Naranjo, Eduardo; Ramírez-Marcial, Neptalí (Instituto de Ecología, A.C., 2004)
The purpose of this study was to estimate mammalian richness and diversity in shaded coffee plantations and tropical rainforest in the community of Loma Bonita, Maravilla Tenejapa, Chiapas, Mexico. We compared the species richness, diversity, relative abundance, and similarity of mammal communities between habitats and seasons. We recorded 953 individuals of 54 mammal species, with predominance of the orders Chiroptera (n=31 species) and Rodentia (n=13 species). During the dry season, species richness (S) and diversity (H´) were higher in rainforest habitat (S=40, H´=3.2) than in coffee plantations (S=31, H´= 2.7). Species richness and diversity were stable during the rainy season in coffee plantations (S=31; H´= 2.6), but declined in the rainforest (S=24; H´=2.3). The most abundant species were the phyllostomid bat Sturnira lilium and the mouse Peromyscus mexicanus in coffee plantations and rainforest, respectively. We found a higher similarity of mammalian communities between habitats in the dry season (IM-H= 0.6) than in the wet season (IM-H= 0.4). In order to relate mammalian diversity and composition with arboreal structure, we characterized both habitat types recording 51 woody species of 25 families, of which 7 species and 4 families were present both in rainforest and coffee plantations (i.e., Musa paradisiaca, Inga pavoniana, Pouteria sapota, Brosimum alicastrum, and Castilla elastica). We only found significant seasonal differences for relative abundance of bats. Because of the high similarity of mammalian richness and diversity between the rainforest and shaded coffee plantations, our results support the previous assumption that the latter are important for maintaining mammalian diversity in transformed ecosystems.